An Overview of Chemical Pesticide Import in Nepal - Khanal, D.; Neupane, S. K.; Poudel, S.; Shrestha, M. (Journal of Agriculture and Environment, 2021)
In 2021, this study has attempted to analyze the trend of pesticide import over two decades in Nepal. Secondary data obtained from Plant Quarantine and Pesticide Management Center were analyzed to know the pesticide import trend. The result showed that the import of pesticides was in increasing trend and the average annual increase in import was 30.48 tons (a.i.) over the last twenty-two years. Fungicide had the highest import followed by insecticide, herbicide and these three groups comprised more than 90% of the pesticide import. The import of insecticide, fungicide, herbicide, organophosphate, mix group pesticide was in increasing trend while that of rodenticide, bactericide was in decreasing trend. The import of synthetic pyrethroid, carbamates, and some new groups like nicotinoids had been increasing in recent years. Although the import of chemical pesticides was increasing in huge amount; import of biopesticide also seems to be in increasing trend. The use of pesticide is still low in Nepal as compared to the global average or other countries however, the effects of its use are greater and hazardous which indicates the need for strong policy implementation for the safe import and use of pesticides.